Sexually Transmitted Infections Surveillance in Pakistan - Sharaf Ali Shah; Arshad Altaf (Journal of the Pakistan Medical Association, 2024)
Sexually transmitted infections (STIs) are transferred fromperson to person by unsafe sexual contact. Some STIs canalso be transmitted through transfusion of unscreenedblood during pregnancy, childbirth, and breastfeeding.1 Untreated STIs can lead to serious health consequences,including human immunodeficiency virus (HIV) andinfertility, and can complicate pregnancy.1 The World Health Organization (WHO) estimates thatmore than one million infections are transmitted everyday worldwide, and the majority of them areasymptomatic.2 Every year, approximately 400 millionnew STI infections are detected, including the fourtreatable STIs, each of which is curable. These arechlamydia, gonorrhoea, syphilis, and trichomoniasis.2 Asignificant proportion of people between 15-49 years ageare estimated to have herpes simplex virus (HSV orherpes) infection of the genital area.3 STIs can also lead tolifelong stigma.2 Hepatitis B virus (HBV) can also betransmitted through unsafe sexual contact and lead tocirrhosis and hepatocellular carcinoma.2 Continued...